PENGARUH PENGELUARAN PEMERINTAH, PERTUMBUHAN EKONOMI DAN PENGANGGURAN TERHADAP KEMISKINAN - Reza Mu’tiqul Azmi; Jihad Lukis Panjawa (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to analyze the effect of economic growth, government spending on education and health, and unemployment on poverty in Indonesia. By using secondary data and timer series in annual form from 1996-2021 and using the Autoregressive Distributed Lag (ARDL) method to estimate the model, the effect of the independent variable on the dependent variable in the short and long term will be known. The results show that in the short term economic growth has a negative and significant effect on poverty and government spending on health has a positive and significant effect on poverty. In the long term economic growth and government spending on education have a negative effect on poverty but not significant, government spending on health has a positive effect on poverty and not significant. While the unemployment variable has a positive and significant effect on poverty.